Integrating OCL and Model Transformations in Fujaba - Stölzel, Mirko; Zschaler, Steffen; Geiger, Leif (Electronic Communications of the EASST, 2007)
This paper discusses the integration of the Dresden OCL Toolkit into the Fujaba Tool Suite. The integration not only adds OCL support for class diagrams but also makes OCL usable in Fujaba's model transformations. This makes Fujaba's model transformations more powerful, completely platform independent and easier to read for developers who are already familiar with OCL. By using the code generator of the Dresden Toolkit, we are able to generate executable Java code from Fujaba's model transformations including the OCL constraints.